Risk Factors for Recurrent Ectopic Pregnancy: A Case - Control Study - Abdullah Karaer; Sabri Cavkaytar; İsmail Mert; Sertaç Batıoğlu (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVES: To investigate the role of epidemiological factors in recurrent ectopic pregnancies. STUDY DESIGN: From January 2003 to February 2005, 205 women with single ectopic pregnancy and 20 women with recurrent ectopic pregnancy were identified. The information collected for each woman included socio-demographic characteristics, smoking status, reproductive, sexual, contraceptive and medical histories (including PID). RESULTS: The risk of recurrent ectopic pregnancy was increased with age, mean of gravidity and history of pelvic surgery. After multivariate analysis, there was no significant association between recurrent ectopic pregnancy and any variables. CONCLUSION: Primary prevention of ectopic pregnancy is the best measure against preventing recurrent ectopic pregnancy. Moreover, for successful secondary prevention, identification of modifiable risk factors for recurrent ectopic pregnancy is important.